Fast Neutron Scattering and Attenuation Technique for Measurement of Void Fractions and Phase Distribution in Transient Flow Boiling - Yuen, Peter S.L. (My University, 1978)
A fast neutron scattering and transmission method for determining void fraction and phase distribution in transient flow boiling was investigated. Shaped aluminum test sections containing water were placed in a fast neutron beam, and the scattered and transmitted flux measured at several locations. Aluminum is relatively neutron transparent and therefore simulated the vapour phase. The aluminum pieces were shaped to represent vapour distributions in some of the main two-phase flow regimes (annular, inverted annular, and stratified). The scattered flux was found to depend primarily on the volume fraction of water (and hence void fraction) in the test section. The transmitted flux profile on the other hand, was sensitive to the distribution of water. The measurements therefore indicated that the cross-section averaged void fraction could be determined from the scattered flux, whereas phase distributions could be determined from the transmitted flux profile . These measurements were followed by a series of experiments in which a test section containing a flowing air-water mixture was placed in the fast neutron beam. Void fractions determined from scattered neutron flux measurements were compared with void fractions measured by trapping the flowing mixture between two quick closing valves and weighing the contents . The neutron scattering technique predicted values i n good agreement with the quick closing valve measurements over the entire range of void fractions .
Title: Fast Neutron Scattering and Attenuation Technique for Measurement of Void Fractions and Phase Distribution in Transient Flow Boiling, Author: Peter S. L. Yuen, Location: Thode